Efektywna promocja własna jako źródło wizerunkowego sukcesu organizacji medialnej – na przykładzie TVN S.A.: Effective self-promotion as a source of image success of a media organization – based on the example of TVN S.A. - Jupowicz-Ginalska, Anna (Management and Administration Journal, 2021)
TVN is certainly one of the most important media organizations in Poland whose action from the very beginning has been characterized by high innovation: both in programming, and its approach to promotional strategy. It often initiated interesting branding solutions, thus becoming an inspiration to other media-market players. In this article I show how skillfully conducted promotional activities affect the image (understood as the success of the entire organization). I focus primarily on the areas of strength and brand recognition. I also present the real achievements of the station and the most important promotional techniques, used by TVN in order to create a strong position in the industry. I confirm the thesis about multi-channel media promotion. It is even possible to observe the convergence of this phenomenon, in which multiple techniques integrate, combine, merge and complement each other, creating a coherent vision of the company and its image. What’s more, each receives promotional support from the "four P" of media marketing: product, price, distribution and promotion.